Perancangan User Experience Aplikasi Portal Beasiswa Mahasiswa berbasis Mobile menggunakan Metode Design Thinking (Studi Kasus: Beasiswa di Universitas Brawijaya) - Muhammad Hardian Ghaffari Nasution; Agi Putra Kharisma; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Education is one of the needs that must be fulfilled by every human being and has an important role in increasing the potential quality of human resources. In fact, many people cannot get an education, especially in higher education. One of the things behind this problem is the inability to afford education, because of high educational cost. Therefore, college dropouts becomes an important issue in Indonesia. Scholarship program might be a solution to the educational cost problem. Students who cannot afford the educational cost can take the advantage of these facilities to help them continue their study. However, there are still problems faced by the students there are confusion and takes time to obtain information of scholarship. Currently, information of scholarships at Universitas Brawijaya are shown on student organization's social media and a website page in the form of articles which are less effective and efficient. Based on these problems, this research aims to design the user experience of a mobile-based student scholarship portal application using the design thinking as an approach method in problem solving that focus and collaborate with potential users. The final results of this research is a high-fidelity prototype solution design. The solution design was evaluated using usability testing which involved ten respondents and User Experience Questionnaire (UEQ) which involved twenty respondents. In usability testing, the results on effectiveness aspects obtain a score of 90.71%, efficiency aspect uses the time-based efficiency calculation of 0.122 goals/sec, and the satisfaction aspects uses System Usability Scale (SUS) with an SUS average score of 89.25. In UEQ, the results obtained are; the average value of the attractiveness scale is 2.37 (excellent), the perspicuity scale is 2.50 (excellent), the efficiency scale is 2.38 (excellent), the dependability scale is 2.28 (excellent), the stimulation scale is of 2.38 (excellent), and the novelty scale of 1.58 (good).